ANALISIS PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN JAMAAH UMROH - Diana Safitri (Multazam : Jurnal Manajemen Haji dan Umrah, 2021)
The competition for travel agencies is growing, in the metro, which competes a lot in providing services to their congregations to continue using this travel agency. The factors that influence the quality of service to the satisfaction of Umrah pilgrims at PT Saudi Patria Wisata Metro are services that are in accordance with the needs of the pilgrims, the services provided by PT Saudi Patria Wisata Metro, affordable prices, affordable locations.